2020
DOI: 10.29082/ijnms/2020/vol4/iss1/250
|View full text |Cite
|
Sign up to set email alerts
|

The Differences of Patient’s Families Perceptions With BPJS Insurance and General About Response Time Nurse’s Based on Triage in the Emergency Room

Abstract: Many families of BPJS or general patients assume that the nurse's response time is slow. The purpose of this study was to determine differences in family perceptions of BPJS and general patients about nurse response time based on triage in emergency room. The method in this study is quantitative descriptive with a comparative approach. The design used was cross-sectional with taking consecutive sampling techniques. The variables studied were differences in family perceptions of BPJS patients and the general ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…With the increase in the number of alarms that do not require an urgent response, the response time of nurses has increased significantly. A study which analyzed the response time of medical staff in the emergency department using a questionnaire completed by the patients found that they considered the response time of the medical staff to be unsatisfactory [50]. An analysis of nurses' response times to patient calls by canceling alarms is presented in [51].…”
Section: Medical Staff Response Time To Alarmsmentioning
confidence: 99%
“…With the increase in the number of alarms that do not require an urgent response, the response time of nurses has increased significantly. A study which analyzed the response time of medical staff in the emergency department using a questionnaire completed by the patients found that they considered the response time of the medical staff to be unsatisfactory [50]. An analysis of nurses' response times to patient calls by canceling alarms is presented in [51].…”
Section: Medical Staff Response Time To Alarmsmentioning
confidence: 99%